Emerging insect-based aquafeed for sustainable African catfish production - Anderson N. Maina; Isaac M. Osuga; Leonard K. Munga; Jonathan M. Munguti; Subramanian Sevgan; Didier K. Barwani; Menaga Meenakshisundaram; Jimmy B. Mboya; Stavroula Bourou; Aikaterini Zachariadi; Vassilios Zachariadis; Rodrigue Yossa; et al. (PLoS ONE, 2025)
The current study assessed the implications of substituting fish meal (FM) with black soldier fly larvae meal (BSFLM) on sustainable African catfish ( Clarius gariepinus ) production. Five isocaloric experimental diets were formulated and 168-days feeding trials were performed with 1400 improved strains of African catfish. Fish fed with 50% BSFLM expressed the lowest and highest feed conversion ratio, and daily weight gain and specific growth rate. Fillets from fish fed diet with 50 and 75% BSFLM inclusion expressed higher lauric (11.4–16.7%) and linoleic acids. Omega-6 fatty acid was 19-fold higher in fillets from fish fed diet with 75%BSFLM. There was 5–8% and 9–11% higher crude protein in fillet from fish fed diet with 50 and 75% BSFLM, respectively. Essential amino acids in the fillets, particularly lysine [11 – 18g/kg] and methionine [11 – 27g/kg] values were significantly higher in catfish fed diet with BSFLM diets than with FM. Diet integrated with 50% BSFLM showed the best return on investment (105.2%) and cost-benefit ratio (1.05). Integration of 50–75% BSFLM into African catfish diet offers a sustainable and cost-effective alternative to conventional fish feed, with promising long-term nutritional and health benefits for the aquaculture industry.